Clinical Observation of the Effect of the Combination of Red Drag-on Fruit Juice (Hylocereus polyrhizus) and Honey on Lowering Blood Pressure: Observasi Klinik Pengaruh Kombinasi Jus Buah Naga Merah (Hylocereus polyrhizus) dan Madu Terhadap penurunan tekanan darah - Meutia Ridha Saputri; Jaka Fadraersada; Maria Almeida; Herman (Jurnal Riseta Naturafarm, 2026)
Pitaya (as known as red dragon fruit in Indonesia) and honey contain high polyphenols and flavo-noids as the main source of antioxidants. Antioxidant compounds in pitaya and honey can reduce systolic and diastolic blood pressure. The aim of this study were to determine the characteristics of gender, age, and Body Mass Index of hypertensive respondents and determine the effect of the combination of pitaya juice and honey on the reduction in blood pressure and Body Mass Index for geriatric hypertensive respondents at the Puskesmas Sempaja Samarinda. This research used quasi-experimental method and data was taken with pre-test and post-test procedures. The data of respondent characteristics shown are women got the highest percentage of 58.9%, middle age of 57.8% and normal weight category (BMI) of 40.7%. The results of descriptive analysis in sys-tolic and diastolic blood pressure from pre-test are 138.64 mmHg and 82.28 mmHg, the post-test are 132.55 mmHg and 77.85 mmHg and decrease in the Body Mass Index of 0.22 kg/m2. The conclusion of this research is the combination of pitaya juice and honey was able to reduce the blood pressure and Body Mass Index